Histerorrafía en un solo plano como alternativa en la cesárea. - Ramírez, Magno Tulio (2015)
Objective: To show that single layer repair of the low transverse uterine incision in similar to the two layer repair. Design: Fifty patients without infectious pathology attended at Maria Auxiliadora Hospital in one year from July 1, 1993 to june 30, 1994 had primary cesarean section. Patients were randomly assigned to either group, with single -layer or two- layer repair of transverse uterine incision. Results: Follow-up of patients did no show differences between the two groups, but for less operative time and longer hospitalization. Conclusion: The single-layer repair of the low transverse uterine incision is a good alternative in cesarean section.